العلاقة التفاعلية بين نظم معلومات دعم القرار ونظام الرقابة الداخلية في المؤسسات الخدمية –دراسة حالة مؤسسة موبيليس- The Interactive Relationship Between Decision Support Systems (dss) And The Internal Control System In Service Institutions - A Case Study Of Mobilis Corporation - سليماني, زناقي; طالب, أحمد فيصل (جامعة الوادي - University of Eloued, 2022)
ملخص: هدفت الدراسة إلى تحديد طبيعة العلاقة التفاعلية بين نظم معلومات دعم القرار ونظام الرقابة الداخلية في المؤسسات الخدمية بالتطبيق على مؤسسة موبيليس، حيث تم التوصل إلى أن هذه العلاقة ليست علاقة متغير تابع بمتغير مستقل ولكنها علاقة تأثير وتأثر في اتجاهين، حيث أن عملية التحسين في أي متغير من شأنها أن تساهم ايجابيا في تحسين أداء المتغير الآخر، على هذا الأساس تقترح الدراسة أن يتم التنسيق والتعاون بين مصممي النظم المختلفة بالمؤسسة، أي أن لا تكون عملية تصميم نظام دعم القرار بالمؤسسة بمعزل عن تصميم وبناء نظام رقابتها الداخلية Abstract: This study aimed to determine the form of the interactive relationship between decision support information systems and the internal control system in service institutions by applying to Mobilis Corporation. It was concluded that this relationship is not the relationship of a dependent variable to an independent variable, but it is an influence relationship in two directions, so that the process of improvement in any variable would contribute positively to improving the performance of the other variable, on this basis the study suggests that coordination and cooperation take place between the designers of different systems in the institution That is, the process of designing an organization's decision support system should not be in isolation from the design and construction of its internal control system.
Keywords: نظام المعلومات ; نظم دعم القرار ; الرقابة الداخلية ; المؤسسات الخدمية ; Information system ; decision support systems ; Internal Control ; service institutions